Low gamma-glutamyl transpeptidase levels at presentation are associated with severity of liver illness and poor outcome in biliary atresia - Song Sun; Shan Zheng; Chun Shen; Rui Dong; Kuiran Dong; Jingying Jiang; Yifan Yang; Gong Chen (Frontiers Media S.A., 2022)
ObjectiveTo investigate the clinical features and prognosis of biliary atresia (BA) with normal or minimally elevated gamma-glutamyl transpeptidase (GGT).MethodsThe clinical data of patients with BA in our hospital between 2012 and 2017 were retrospectively studied. The patients were divided into a low-GGT group (GGT ≤ 300 IU/L) and a high-GGT group (GGT > 300 IU/L) according to the preoperative GGT level. The perioperative clinical parameters, the postoperative jaundice clearance within 6 months, and the 2-year native liver survival were compared among the groups.ResultsA total of 1,998 children were included in this study, namely, 496 in the low-GGT group and 1,502 in the high-GGT group. The ages and weights at the surgery in the low-GGT group were significantly lower than those in the high-GGT group (64.71 ± 21.35 vs. 68.64 ± 22.42 days, P = 0.001; 4.67 ± 1.03 vs. 4.89 ± 0.98 kg, P < 0.001). The levels of serum ALP, ALT, and AST in the low-GGT group were significantly higher than those in the high-GGT group before and 2 weeks after the surgery (ALP: 647.52 ± 244.10 vs. 594.14 ± 228.33 U/L, P < 0.001; ALT: 119.62 ± 97.14 vs. 96.01 ± 66.28 U/L, P < 0.001; AST: 218.00 ± 173.82 vs. 160.71 ± 96.32 U/L; P < 0.001). The INR of the low-GGT group was higher than that of the high-GGT group (1.05 ± 0.34 vs. 0.98 ± 0.20, P < 0.001), while FIB was lower than the high-GGT group (2.54 ± 0.67 vs. 2.73 ± 1.44 g/L; P = 0.006). The decreasing amplitude of TB and DB within 2 weeks after surgery in the low-GGT group was smaller than those in the high-GGT group (TB: 51.62 ± 71.22 vs. 61.67 ± 53.99 μmol/L, P = 0.003; DB: 33.22 ± 35.57 vs. 40.20 ± 35.93 μmol/L, P < 0.001). The jaundice clearance rate in the low-GGT group was significantly lower than that in the high-GGT group at 1, 3, and 6 months after surgery (17.70 vs. 26.05%; 35.17 vs. 48.58%; 38.62 vs. 54.64%, P < 0.001). In addition, the 2-year native liver survival rate in the low-GGT group was significantly lower than that of the high-GGT group (52.5 vs. 66.3%, P < 0.001 HR 1.80, 95% CI 1.38-2.33).ConclusionCompared to patients with high GGT, patients with normal or minimally elevated pre-operative GGT in BA were found to have poorer pre-operative liver function parameters, and post-operatively had lower jaundice clearance rates and worse 2-year native liver survival. This suggests a lower GGT at presentation in biliary atresia could be a sign of more severe liver injury.